The effect of engineered surface topography on the tribology of CFR-PEEK for novel hip implant materials. (September 2016) - Wyatt, Hayley; Elliott, Marc; Revill, Paul; Clarke, Alastair
Abstract: Carbon-fibre-reinforced polyether ether ketone (CFR PEEK) has the potential to improve the wear resistance of orthopaedic implants and its performance can be further enhanced by surface texturing. This scoping study investigates the effects of surface textures on the friction behaviour of CFR PEEK, using screening testing to identify textures suitable for development for acetabular cup applications. Six surface textures were designed and applied to CFR PEEK discs using laser surface texturing, with the dimple diameter and area coverage being varied. These textures were tested using pin on disc testing, with a cobalt chrome pin representing the femoral head. Coefficient of friction and surface characterisation were used to assess the performance of each texture. The results from the study demonstrated that all textures reduced the coefficient of friction compared to the plain material. The variation in the performance of the different textures highlighted a need for optimum texture characteristics to be found. 150 μm circular dimples, spaced 175–200 μm apart with an area coverage of 10–15% gave the best performance in saline lubrication at a contact pressure of 2 MPa and sliding speed of 50 mm/s. Tests should be repeated in a proteinaceous testing medium at various contact pressures and speeds. Highlights: Surface texturing of CFR PEEK for use in artificial hip joints was investigated. Results found all surface textures to reduce the coefficient of friction. The effectiveness of each texture varied based on design characteristics. Surface textures need to be optimised to significantly improve implant design.